2003
DOI: 10.3748/wjg.v9.i4.736
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hepatitis B virus infection on human sperm chromosomes

Abstract: HBV infection can bring about mutagenic effects on sperm chromosomes. Integrations of viral DNA into sperm chromosomes which are multisites and nonspecific, can further increase the instability of sperm chromosomes. This study suggested that HBV infection can create extensively hereditary effects by alteration genetic constituent and/or induction chromosome aberrations, as well as the possibility of vertical transmission of HBV via the germ line to the next generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
5
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 35 publications
5
82
5
7
Order By: Relevance
“…The vertical transmission of HBV from the HBsAg-positive fathers to the infants also had no significant effect on the aforementioned newborn indicators (Table IV). Previous studies have shown that an HBV-infected male, whose sperm chromosome aberration rate is significantly increased compared with healthy controls, may experience an increased risk of infertility, abortion, stillbirth, perinatal mortality and fetal malformations (18)(19)(20)(21). The present results are not consistent with these findings.…”
Section: P-value T-value --------------------------------------------contrasting
confidence: 99%
“…The vertical transmission of HBV from the HBsAg-positive fathers to the infants also had no significant effect on the aforementioned newborn indicators (Table IV). Previous studies have shown that an HBV-infected male, whose sperm chromosome aberration rate is significantly increased compared with healthy controls, may experience an increased risk of infertility, abortion, stillbirth, perinatal mortality and fetal malformations (18)(19)(20)(21). The present results are not consistent with these findings.…”
Section: P-value T-value --------------------------------------------contrasting
confidence: 99%
“…This result suggests that a risk of vertical transmission of HBV [with the father being HBsAg (+)] had no significant effect on the fetus in the above aspects (see the results in Table 4). Our conclusion contradicts that of many other researchers in which chromosome aberration in patients with HBV infection was suggested to be a significant risk factor for infertility, spontaneous abortion, fetal death, fetus malformation, and perinatal infant mortality (Livezey et al, 2002;Huang et al, 2003;Vicari et al, 2006;Ye et al, 2014).…”
Section: General Health Status Of Newbornscontrasting
confidence: 99%
“…Vertical transmission from father to child is more likely to occur when the father is HBsAg-, HBeAg-, and HBcAb-positive, and it has become the second most important mechanism of vertical transmission (just below mother-to-child vertical transmission) (Komatsu et al, 2009). The research of Huang et al (2003) suggested that infection by HBV could cause chromosomal mutation in patient sperm, and that integration of HBV DNA into sperm chromosomes is a random and multi-locus event, increasing the instability of sperm chromosomes and causing widespread influence lasting for generations. Other studies (Ali et al, 2005;Takegoshi and Zhang, 2006;Komatsu et al, 2009) indicated that infants with HBsAg (+) fathers were the highest risk group for vertical transmission.…”
Section: Hbv Vertical Transmission From Father To Infant and Its Tranmentioning
confidence: 99%
“…Furthermore, the results indicated that neonatal infant HBV vertical transmission and the presence of HBsAg in the father exerted no statistically significant effects on the aforementioned indicators (Table IV). Previous studies have found that the rate of sperm chromosome aberrations in fathers infected with HBV was significantly higher compared with healthy controls, while the presence of HBV can also increase the rates of infertility, miscarriage, stillbirth, perinatal child mortality and the risk of fetal malformations (16,(20)(21)(22); however, the results of the present study were different. The results demonstrated that the use of antiviral nucleoside analogs prior to pregnancy was safe in fathers.…”
Section: Discussioncontrasting
confidence: 56%
“…From these studies, the possibility of father-to-child transmission of HBV was identified, and with further research, the existence of HBV father-to-child transmission was confirmed at the molecular level. The results by Huang et al (16) revealed that a HBV infection can cause sperm chromosome mutations. The integration between HBV DNA and the sperm chromosome was random and at multiple loci, which further increases the instability of the chromosomes, indicating that HBV infection may have a widespread impact by altering the genetic composition generation after generation.…”
Section: Discussionmentioning
confidence: 97%